2014
DOI: 10.1364/oe.22.021958
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon–induced internal modification of silicon by erbium-doped fiber laser

Abstract: Three-dimensional bulk modification of dielectric materials by multiphoton absorption of laser pulses is a well-established technology. The use of multiphoton absorption to machine bulk silicon has been investigated by a number of authors using femtosecond laser sources. However, no modifications confined in bulk silicon, induced by multiphoton absorption, have been reported so far. Based on results from numerical simulations, we employed an erbium-doped fiber laser operating at a relatively long pulse duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…However, beyond 0.96 J, it was observed that the Er:YAG laser interacted with silicon assisted by a water layer and was thermally damaged. For systematic investigation, we set the pulse energy to the maximum (1.16 J) and used pulse numbers of 1, 3,4,6,8,12,14,15,16,18,20, and 22. The whole experiment was repeated three times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, beyond 0.96 J, it was observed that the Er:YAG laser interacted with silicon assisted by a water layer and was thermally damaged. For systematic investigation, we set the pulse energy to the maximum (1.16 J) and used pulse numbers of 1, 3,4,6,8,12,14,15,16,18,20, and 22. The whole experiment was repeated three times.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, subsurface modification of silicon by 1.55 lm lasers was reported, where nonlinear light absorption was utilized. 7,8 Sreenivas et al used an 800 fs laser at 1.55 lm to induce subsurface damage by initiating twophoton absorption and self-focusing. 7 Similarly, Verburg et al reported that silicon subsurface modification was achieved by using a 3.5 ns laser with a wavelength of 1.549 lm via two-photon absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, wavelength, pulse duration, and focusing conditions are typically chosen such that the absorption takes place mainly inside the volume of the wafer [10,13]. In the first example, the laser acts as volume heat source that generates a stress field which causes the wafer to crack [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the first example, the laser acts as volume heat source that generates a stress field which causes the wafer to crack [10,11]. In the case of stealth dicing [12,13], pulsed laser light is focused tightly below the surface to generate a defect inside the volume. To separate the dies, the crack or the defects can be guided by translating the beam across the wafer.…”
Section: Introductionmentioning
confidence: 99%